Knowledge and awareness of stroke and associated factors in the Saudi general population: a cross-sectional study - Alzayer, Reem; Barakat, Muna; Jirjees, Feras; Alhamdan, Aqeelah; Aloraifej, Shatha; Cherri, Sara; Mansour, Sara; El Khatib, Sami; Kharaba, Zelal; Rahal, Mohamad; Hallit, Souheil; Malaeb, Diana; et al. (Frontiers in Neurology, 2023)
Introduction Stroke is a major cause of death and disability globally and in Saudi Arabia as well. Prevention and management of stroke depend highly on raising knowledge and awareness about the disease. Purpose The purpose of this study was to evaluate Saudi adult's knowledge and awareness about stroke and determine the associated factors. Materials and methods A cross-sectional online survey was conducted in May–July 2022 among Saudi citizens. Assessments of stroke knowledge about risk factors, symptoms, and response to stroke symptoms were evaluated. Logistic regression was conducted to assess the association between the socio-demographic characteristics and knowledge. Results A total of 389 participants were enrolled with the majority (81.7%) being male participants. Less than half of the study subjects (43.3%) identified four out of five correct answers related to general knowledge about stroke. Almost all the participants were able to identify at least one risk factor associated with stroke. The majority of the participants (81.2%) believed that physical inactivity was the most common risk factor associated with stroke. Approximately three-quarters of participants considered difficulty speaking and understanding speech, followed by the sudden loss of consciousness as the most common stroke manifestation. Participants with a history of hypertension, dyslipidemia, and obesity had significantly higher odds of identifying at least one early stroke symptom (OR 2.271 [95% CI 1.402 3.677], 2.059 [95% CI 1.273 3.328], and 2.665 [95% CI 1.431 4.963], respectively). Conclusion Our study revealed that participants have good knowledge about stroke. Nonetheless, further efforts are required to raise awareness and educate the public to optimize and ensure better treatment outcomes.